2012
DOI: 10.1523/jneurosci.1651-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Molecular-Anatomical Evidence for GABAergic Influence on Axon Initial Segment of Cerebellar Purkinje Cells by the Pinceau Formation

Abstract: The axon initial segment (AIS) of cerebellar Purkinje cells (PCs) is embraced by ramified axons of GABAergic basket cells (BCs) called the pinceau formation. This unique structure has been assumed to be a device for the modulation of PC outputs through electrical and/or GABAergic inhibition. Electrical inhibition is supported by enriched potassium channels, absence of sodium channels, and developed septate-like junctions between BC axons. The neurochemical basis for GABAergic inhibition, however, has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 67 publications
2
42
0
2
Order By: Relevance
“…Given the strong inhibitory modulation of Ca v 2.1 by CaBP1 (Lee et al, 2002), CaBP1/CD may be important for shaping presynaptic Ca 2+ signals that regulate precise timing of Purkinje cell inhibition. Although morphological evidence argues against a role for the pinceaux in the release of GABA onto Purkinje neurons (Iwakura et al, 2012), it has been proposed that the pinceau mediates a “field effect” whereby electrical activity in the basket cell terminal influences the membrane potential of the ensheathed Purkinje neurons (Korn and Axelrad, 1980). Although we did not observe gross motor impairment in C-KO mice, further analyses will be required in these mice to define a potential role of CaBP1/CD in controlling cerebellar output.…”
Section: Discussionmentioning
confidence: 99%
“…Given the strong inhibitory modulation of Ca v 2.1 by CaBP1 (Lee et al, 2002), CaBP1/CD may be important for shaping presynaptic Ca 2+ signals that regulate precise timing of Purkinje cell inhibition. Although morphological evidence argues against a role for the pinceaux in the release of GABA onto Purkinje neurons (Iwakura et al, 2012), it has been proposed that the pinceau mediates a “field effect” whereby electrical activity in the basket cell terminal influences the membrane potential of the ensheathed Purkinje neurons (Korn and Axelrad, 1980). Although we did not observe gross motor impairment in C-KO mice, further analyses will be required in these mice to define a potential role of CaBP1/CD in controlling cerebellar output.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10%-20% of BC axonal terminals cover the AIS at the pinceau; the majority are separated from PC AIS by astrocyte processes (40) (Figure 8B). This unique anatomic configuration of astrocytes at the pinceau is thought to play a crucial role in BCinduced ephaptic inhibition (40).…”
Section: Sca1mentioning
confidence: 99%
“…This unique anatomic configuration of astrocytes at the pinceau is thought to play a crucial role in BCinduced ephaptic inhibition (40). To study the neuronal-glial interface, we costained the cerebellar sections with GFAP and calbindin.…”
Section: Sca1mentioning
confidence: 99%
“…Although the latter structure is unique, recent precise morphological and immunohistochemical analyses have shown that typical synaptic contact at the AIS of cerebellar Purkinje cells is very rare. Moreover, the alpha1 subunit of the GABA A receptor, a subunit in Purkinje cells, did not form detectable clusters along the AIS, indicating that Purkinje cells do not receive GABA-mediated synaptic inhibition from basket cells on the AIS [36].…”
Section: Discussionmentioning
confidence: 96%